Is Italian Dentists’ Knowledge of Enamel Development Defects Adequate? A Nationwide Survey - Claudia Salerno; Guglielmo Campus; Nicole Camoni; Silvia Cirio; Alberto Caprioglio; Maria Grazia Cagetti (International Dental Journal)
Objectives: Correct identification and management of Developmental Defects of Enamel (DDEs) are essential to provide the best possible treatment. The present survey aims to investigate Italian dentists’ knowledge of DDEs, their ability to recognise the different clinical pictures, and to choose the most appropriate clinical approach. Methods: A cross-sectional survey was planned based on a questionnaire including 27 closed-ended questions, and that proposed 4 clinical pictures, molar incisor hypomineralisation (MIH), amelogenesis imperfecta (AI), dental fluorosis (DF), and an initial caries lesion (ICL). It was distributed by e-mail to all Italian dentists (N = 63,883) through the Italian Federation of Doctors and Dentists. Discrete variables were expressed as absolute and relative frequencies (%). A multivariate analysis assessed whether socio-demographic variables correlated with the answers’ truthfulness. Results: About 5017 questionnaires were included and analysed. Although 90.19% of the sample stated that they had received information on DDEs, a significant percentage did not recognise MIH (36.36%), AI (48.34%), DF (71.50%), and ICL (46.62%). Only 57.07% correctly classified enamel hypomineralisation as a qualitative defect, and even fewer, 54.45%, classified enamel hypoplasia as a quantitative defect. According to the logistic regressions, female dentists, dentists who treat mainly children and received information about DDEs, were more likely to recognise the 4 clinical pictures (P < .01). Conclusions: Italian dentists showed many knowledge gaps on DDEs that need to be filled; those who received formal training were more capable of correctly identifying the defects and were more likely to prescribe an appropriate management approach for the defects. Clinical significance: Increasing university courses and continuing education on diagnosing and managing DDEs seems reasonable to fill the knowledge gap on DDEs.